ABNORMAL RETURNS AT CALENDAR TURNING POINTS AT THE MALAYSIAN EXCHANGE - Zainudin Arsad (Program Studi Statistika Unisba, 2004)
In recent years overwhelming evidence has been documented on the existence of abnormal stock returns. These anomaliestend to occur at turning points in time. Although these artificial moments have little impact on economy, investors maydeem them important and behave accordingly and consequently the notion that stock returns are random as claimed by theEfficient Market Hypothesis may be questioned. The primary objective of this paper is to investigate the January effect fora few indices at the Main Board of the Malaysian Exchange. The results broadly support similar evidence documented formany countries as the January effect appears to be present in our data set. Since there is no capital gain tax in Malaysia, thetax-loss selling hypothesis cannot explain the January effect. Instead, the anomaly may be attributed to the marketintegration hypothesis since the January effect is also a worldwide phenomenon.